The Role of Intensive Islamic Courses in Strengthening Religious Foundation Among Orphaned Children: a Case Study Of Yaa Bunayya Orphanage Under Mutiara Cahaya Qolbu Foundation in Teluk Dalam - Lubis, Hasan Hamzah; Tumanggor, Ilham; Siregar, Taufiq Hidayat; Imam Azhar (As-sunnah: Jurnal Pengabdian Masyarakat, 2025)
This study examines the critical role of intensive Islamic educational programs in establishing religious foundations among orphaned children in minority Muslim communities. Using an Asset-Based Community Development (ABCD) methodological framework, we conducted a detailed investigation at Yaa Bunayya Orphanage, operated by the Mutiara Cahaya Qolbu Foundation in Teluk Dalam, South Nias, Indonesia—a region where Muslims constitute only 2.4% of the population. Through systematic observation, structured interviews with community stakeholders, and documentation analysis during Ramadan-based community service initiatives, we identified significant educational challenges including limited qualified instructors, insufficient learning resources, and geographical isolation from established Islamic educational institutions. The implementation of an accelerated Islamic boarding school program ("pesantren kilat") revealed high enthusiasm for religious education among orphaned children, particularly among recent converts who demonstrated exceptional achievement in Islamic knowledge competitions. Data indicates that structured religious education interventions positively impact children's spiritual development, ethical conduct, and religious practice adherence in religiously diverse environments. This research contributes to understanding effective approaches for Islamic educational development in minority contexts, highlighting the importance of pedagogical innovation, community engagement, and tailored educational strategies that respond to specific socio-cultural environments while addressing resource constraints. These findings offer valuable insights for religious education stakeholders working in pluralistic societies and marginal Muslim communities